Color compression in video registration and security systems - Kazantsev, Nikolai S; Degtyrev, Vladimir M (2009 5th Central and Eastern European Software Engineering Conference in Russia, 2009)
This research work refers to solution of the practical security, anti-terrorist fighting problems, providing effective tools against different non-authorized penetrations. From the informatics and the software points of view these problems are linked to the image processing and creating of the compression algorithms applicable for the video array frames obtained by standard registration systems. Compression solutions become crucially important when the temporal evolution of the video stream exceeds the traffic capacity of the communication network. All algorithms and methods known and exploited nowadays are unable to meet the reliable security requirements. The MPEG and the MPEG4 compression codes distort the initial image. Fragmentation or splitting the video stream into separate frames with the subsequent application of the ordinary DCT or DWT procedures provides better compression rate, but the quality of the image still remains rather poor with no chance for creating a justified and documented personal identification protocol. The main research objective of this paper is providing significant reduction of the information traffic within a standard security registration system (a network of about 10 cameras and microphones relayed to an operating server) possibly maintaining the highest quality of records in the server. The basic image processing approach we exploited is to maintain of the highest resolution degree for the main part of the object we survey (for example man's face or figure) whilst minimizing the information traffic from the image background by its artificial substitution with a homogeneous color filling. This method allowed obtaining significant compression rate already (up to 7000) and presently we are carrying on even more promising studies on this subject.